Peran Pinjaman Bank Terhadap Sektor Riil (Pendekatan Vector Autoregressive) - Aula Ahmad Hafidh (Universitas Negeri Yogyakarta, 2007)
This paper examines how bank lending channel could affected the real sector. The result shows that bank lending have positive influence in the Indonesia real sector. Using Vector Autoregressive (VAR), bank lending affect real sector with time lag. In this paper, real sector divided into two block, household and firm. Household faster to react in increasing bank lending by consumption rise.